Path Planning under The Hull bottom of Painting Robot Based on Heuristic Multi-robot Cooperation in Ship Manufacturing - Song, Lifei; Sun, Hao; Xu, Kaikai; Shi, Xiaoqian; Zhou, Yongqing (Manufacturing Technology Journal, 2022)
In the whole world, the economic loss caused by hull corrosion is enormous. Ship painting has become an important part of ship manufacturing process because it can effectively alleviate the corrosion of ship. The manual painting has disadvantages both in the quality and the efficiency. However, the research of automatic sprayers for a ship hull is not widely used because of the complex environment in the shipyard dock and the huge differences in both size and shape of ships to be repaired. Therefore, this paper pro-posed a new method: according to the ship size and blocks distribution in the blocks' layout of ship yards, the grid method was used to generate the map model; to solve the problems of high rerouting rate, low coverage and large consumption of calculation in the global path planning, a regional division method was proposed to divide the whole area; to shorten the dock occupancy time, a path planning algorithm based on multi robots heuristic cooperation was proposed. Simulation results and experi-mental data show that the full coverage path planning algorithm proposed in this paper has satisfactory adaptability.
Keywords: Spraying robot for hull bottom; Area coverage path planning; Regional decomposition; Multi robots heuristic cooperation; Grid method